Fluctuations in the Rate of Industrial Invention - Merton, Robert K. (Quarterly Journal of Economics, 1935)
I. Socio-economic problems of rates of invention and shifts of inventive interest, 454; limitations of the use of patent statistics as indexes of the rate of invention, 455. — II. The data used, 457; analysis of the data, 458; pattern of technical change within an industry, 460. — III. Factors which account for this pattern, 464.